2011
DOI: 10.1093/humrep/der415
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate and normal sized CGG repeat on the FMR1 gene does not negatively affect donor ovarian response

Abstract: No negative effect was observed for intermediate-sized CGG repeats on ovarian stimulation and clinical outcome using a non-confounding model of oocyte donation. These results disagree with previous studies performed on infertility patients. Owing to the present study, fragile X genetic screening should not be considered for prediction of response to ovarian stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…We employed an analytic technique that focused on the larger allele as the primary predictor while covarying for the size of the smaller allele, which is the method that has been used most widely in the extant literature (Gleicher et al, 2009a,b; Lledo et al, 2012; Voorhuis et al, 2014; Schufreider et al, 2015). This strategy was successful in detecting robust CGG associations in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed an analytic technique that focused on the larger allele as the primary predictor while covarying for the size of the smaller allele, which is the method that has been used most widely in the extant literature (Gleicher et al, 2009a,b; Lledo et al, 2012; Voorhuis et al, 2014; Schufreider et al, 2015). This strategy was successful in detecting robust CGG associations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a variety of possible analytic methods to account for the presence of two X chromosomes in females, there is little consensus in the field as to which analytic technique is optimal. We selected this analytic technique based on established precedent, as this is the most common method used to account for two alleles in females in the extant literature (Gleicher et al, 2009a,b; Lledo et al, 2012; Voorhuis et al, 2014; Schufreider et al, 2015). We did not have activation ratio data available (i.e., the percent of cells carrying any given allele on the active X chromosome), which prevented us from employing other techniques that account for the relative influence of each allele (i.e., Allen et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…5,13 Prior investigations of young egg donors reported conflicting results. [14][15][16] These studies, however, did not include donors who were biallelic low in FMR1. Monoallelic low FMR1 donors also in this study did not yet demonstrate significant differences in FOR between carriers of low alleles and donors who lacked such alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, workers in the neurological field could not find any atypical phenotype association below 45 CGG repeats [87]. Some studies have shown, however, that reproductive function may be significantly impacted in this range [36]; however, other studies have shown no obvious impact [22,58]. The American College of Obstetrics and Gynecology Genetics Committee, and the American College of Medical Genetics (ACMG), explicitly state that an FMR1 CGG repeat length of <45 'is not associated with an abnormal phenotype' [66].…”
Section: The Cgg Mutationsmentioning
confidence: 98%
“…Among the three mutation ranges investigated (premutation, intermediate and high normal) none showed a statistically significant association with infertility nor with ovarian reserve indicators. Slightly earlier, Lledo et al also published results on the use of FMR1 screening in young oocyte donors in predicting the ovarian follicular development [58]; numerous papers on the other hand report a substantial link between FMR1 mutations and ovarian reserve [11,33,86].…”
Section: Cgg Mutations and Biomarkers Of Ovarian Reservementioning
confidence: 99%